Distal radius articular fractures: a comparison between ORIF with angular stability plate and percutaneous Kirschner wires. - Tronci, Vincenzo; Campochiaro, Gabriele; Gazzotti, Gabriele; Rebuzzi, Manuela; Tsatsis, Christos; Catani, Fabio (Acta Biomedica Atenei Parmensis, 2013)
Purpose of the study: To analize and compare vantages and disadvantages in long-term of two different  techniques to treat distal radius articular fractures: ORIF with plate versus percutaneous pinning with K-wires. Materials and Methods:We reviewed 77 distal radial articular fractures treated surgically from 2005 to 2009. Fractures were divided in two homogeneous groups according to patient age, gender, fracture-type and follow-up. The first group was treated with ORIF using angular stability volar plate, while the second one with closed reduction, K-wires percutaneous pinning and ante-brachial plaster casting. Functional outcomes were assessed with MAYO and DASH score, wrist range-of-movement and handgrip. Radiographic parameters were calculated in the post-operative and long-term x-rays. Results: ORIF group showed better mean DASH and MAYO score, range of movement and handgrip strength compare to K-wires group. Expecially in type C fractures and in younger patients (